ANALISIS TINDAK TUTUR LOKUSI, ILOKUSI, DAN PERLOKUSI DALAM PROSES PEMBELAJARAN BAHASA INDONESIA DI KELAS XI MIPA 7 SMA N 7 DENPASAR TAHUN PELAJARAN 2018/2019 - Adhiguna, I Made Pradipta; Susrawan, I Nyoman Adi; Erawan, Dewa Gede Bambang (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2019)
This research is descriptive research with the purposes; (1) Obtaining objective illustration about locutionary, illocutionary, and perlocutionary speech action in the learning process of Indonesian of eleventh grade MIPA 7 of SMAN 7 Denpasar in academic year 2018/2019. (2) Finding out the factors that influence the appearance of locutionary, illocutionary, and perlocutionary speech action in the Indonesian learning process of eleventh grade MIPA 7 of SMAN 7 Denpasar in academic year 2018/2019. The data collection was done by observation, interview and record techniques. The obtained data were analyzed by qualitative descriptive. The locutionary speech acts that spoken by teacher and student in the learning process of Indonesian were 27 utterances, the illocutionary were 36 utterances and perlocusionary   were 36 utterances, teacher and student deliver their speeches in the classroom based on their speech mode which is to convey intentions to interlocutor and the emergence of perlocutionary speech acts in the learning process of Indonesian was influenced by two factors; the teacher who has extensive knowledge about perlocutionary speech acts, so that the teacher could use the speech acts in the learning process, teacher and student deliver their speeches in the class room based on their speech mode with the purpose of the speech which is delivered to have power of influence or effect for interlocutor.